Analisis perkuliahan daring mahasiswa PJKR Universitas PGRI Semarang sebagai dampak pandemi covid 19 - Setiyawan; Kresnapati, Pandu; Aji Setyawan, Danang (Edu Sportivo: Indonesian Journal of Physical Education, 2020)
The purpose of conducting this research is to obtain data on the form of lectures and the results of information on students' efforts to take part in online lectures on PJKR students at the University of PGRI Semarang as a covid effect 19. The research method uses quantitative descriptive using survey methods. Data collection techniques using a questionnaire. The subjects in this study were PJKR University PGRI Semarang students in the second, fourth and sixth semesters. Research conducted obtained the following results: (a) Aspects of the distribution of students in the second semester 47.7%, semester four 21.2% and semester six 31.1%. (b) The most widely used application aspects are Zoom 34.7%, SIP 41.2%, SPADA 1.3% and Google Classroom 22.8%. (c) The duration of online learning is more than 60 minutes 18.6%, 30 minutes to 60 minutes 64.8% and under 30 minutes 16.6%. (d) Material aspects, namely: easy to understand 71.2% and material difficult to understand 28.8%. (e) Aspects of student readiness, in the ready category of 20.9%, quite ready 52.4%, less ready 26.7%. (f) The biggest obstacle for students is challenging the signal of 58.9%, quota of 25.3%, and time of 15.8%. From the research that has been carried out it can be concluded: (1) The form of lectures conducted at the PJKR Study Program of the University of PGRI Semarang utilizes online learning platforms such as Zoom, Google Classroom, SPADA, and SIP. While for field practice lectures using video and assignment forms, (2) The efforts of students to take part in online learning are quite good with the acquisition being quite ready and the percentage is 52.4%.